Autophagy positively regulates DNA damage recognition by nucleotide excision repair - Qiang, Lei (Autophagy, 2015)
Macroautophagy (hereafter autophagy) is a cellular catabolic process that is essential for maintaining tissue homeostasis and regulating various normal and pathologic processes in human diseases including cancer. One cancer-driving process is accumulation of genetic mutations due to impaired DNA damage repair, including nucleotide excision repair. Here we show that autophagy positively regulates nucleotide excision repair through enhancing DNA damage recognition by the DNA damage sensor proteins XPC and DDB2 via 2 pathways. First, autophagy deficiency downregulates the transcription of XPC through TWIST1-dependent activation of the transcription repressor complex E2F4-RBL2. Second, autophagy deficiency impairs the recruitment of DDB2 to ultraviolet radiation (UV)-induced DNA damage sites through TWIST1-mediated inhibition of EP300. In mice, the pharmacological autophagy inhibitor Spautin-1 promotes UVB-induced tumorigenesis, whereas the autophagy inducer rapamycin reduces UVB-induced tumorigenesis. These findings demonstrate the crucial role of autophagy in maintaining proper nucleotide excision repair in mammalian cells and suggest a previously unrecognized tumor-suppressive mechanism of autophagy in cancer.